6th National Occupational Injury Research Symposium: Advancing Occupational Injury Research Through Integration and Partnership. (February 2017) - Castillo, Dawn N.; Schuler, Christine R.; Menéndez, Cammie Chaumont
Abstract: Introduction: The National Occupational Injury Research Symposium (NOIRS) is the only regularly held forum exclusively dedicated to occupational injury research and prevention. Method: The 2015 conference theme, advancing occupational injury research through integration and partnership, shaped the conference and is reflected in articles selected for this special issue. Results' Conclusion: The 6th NOIRS, held May 19–21, 2015, brought together more than 250 researchers, occupational safety practitioners and students to share and discuss occupational injury research. Articles in this special issue highlight some of the research presented at the conference, reflect multiple scientific disciplines and approaches, cover a breadth of occupational injury causes and worker populations, and provide examples of research advanced by partnerships. Practical Applications: The next NOIRS, tentatively scheduled for 2018, will build upon the theme of integration and partnership as well as feedback from conference attendees.